Status of endangered and threatened caribou on Canada's arctic islands - Gunn, Anne; Miller, Frank L.; Nishi, John (Rangifer, 2000)
Caribou (Rangifer tarandus) on the Canadian Arctic Islands occur as several populations which are nationally classified as either endangered or threatened. On the western High Arctic (Queen Elizabeth) Islands, Peary caribou (R. t. pearyi) declined to an estimated 1100 caribou in 1997. This is the lowest recorded abundance since the first aerial survey in 1961 when a high of ca. 24 363 caribou was estimated on those islands. Peary caribou abundance on the eastern Queen Elizabeth Islands is almost unknown. On the southern Arctic Islands, three caribou populations declined by 95-98% between 1973 and 1994 but our information is unclear about the numerical trends for the two other populations. Diagnosis of factors driving the declines is complicated by incomplete information but also because the agents driving the declines vary among the Arctic's different climatic regions. The available evidence indicates that severe winters caused Peary caribou die-offs on the western Queen Elizabeth Islands. On Banks Island, harvesting together with unfavourable snow/ice conditions in some years accelerated the decline. On northwestern Victoria Island, harvesting apparently explains the decline. The role of wolf predation is unknown on Banks and notthwest Victoria islands, although wolf sightings increased during the catibou declines. Reasons for the virtual disappearance of arctic-island caribou on Prince of Wales and Somerset islands are uncertain. Recovery actions have started with Inuit and Inuvialuit reducing their harvesting but it is too soon to evaluate the effect of those changes. Recovery of Peary caribou on the western Queen Elizabeth Islands is uncertain if the current trends toward warmer temperatures and higher snowfall persist.